IMPROVING THE IMAGE OF THE GENERAL ELECTION COMMISSION (KPU) AFTER ISSUING A REGULATION PROHIBITING LEGISLATIVE CANDIDATES CONVICTED OF CORRUPTION FROM CONTESTING THE 2019 ELECTIONS - Diah Widyawati; Ahmad Sihabudin; Heri Budianto (Bajang Institute, 2024)
This research focuses on when the General Election Commission (KPU) issued KPU Regulation (PKPU) Number 20/2018 on the Nomination of Members of the House of Representatives, Provincial House of Representatives, and Regency/City Regional House of Representatives. This PKPU is the “PKPU on Candidates of Former Corruption Convicts.